2020
DOI: 10.22492/ijpbs.5.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use as Self-Therapy or Alternative Mental Help-Seeking Behavior

Abstract: Social media use is pervasive in many developed societies. Social Media is a form of digital media and expansive platform that allows users to share information, and socialize with other users (Anderson & Jiang, 2018). There are multiple formats of social media being used by society today. Social networking has become such a large part of the everyday life of people such that many individuals repeatedly post or check their social media accounts. College students use social media to create virtual friendships a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Consistent with the stereotype embodiment theory (Levy, 2009), as older adults gain access to more diverse social cultures and are exposed to more forms of social interaction through their phones, the harm of such negative stereotypes on social isolation will be reduced. Cellphone use also facilitates the use of coping strategies by providing a channel for seeking help (Gere et al, 2020). Older adults can easily obtain more news and information through their cellphones, which could help them understand the changing world.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the stereotype embodiment theory (Levy, 2009), as older adults gain access to more diverse social cultures and are exposed to more forms of social interaction through their phones, the harm of such negative stereotypes on social isolation will be reduced. Cellphone use also facilitates the use of coping strategies by providing a channel for seeking help (Gere et al, 2020). Older adults can easily obtain more news and information through their cellphones, which could help them understand the changing world.…”
Section: Discussionmentioning
confidence: 99%
“…All twelve articles were empirical studies. Of these, five studies utilized a quantitative approach through the survey method (Chen et al, 2020;Stawarz et al, 2019;Gere et al, 2019;Naslund et al, 2019) and the pre-post-test survey method (Thompson et al, 2021). Four studies reported qualitative evaluation, where two of them used content analysis method (Latha et al, 2020;Saha et al, 2019), one used focus group method (O'Reilly et al, 2019), one used semi-structured interview (Noorwali et al, 2022) and one used crosssectional analysis (Pretorius et al, 2022).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Based on the discussion above, we believe that there is a promising potential that social media can be beneficial for youth to communicate about mental health and to seek help from others in dealing with their mental health concerns. Nevertheless, empirical research on the use of social media in mental health communication is still scarce in the current literature, except for a few studies investigating social media use for promoting mental health awareness (e.g., Latha et al, 2020;O'Reilly et al, 2019;Pretorius et al, 2022;Saha et al, 2019;Plaisime, et al, 2020) and its impact on help-seeking behavior (Gere et al, 2019;Pretorius et al, 2022;Thompson et al, 2021;Chen et al, 2022;Naslund et al, 2019). Only a few of these studies, however, focus on the youth population (Plaisime et al, 2020;O'Reilly et al, 2019;Chen, et al, 2022;Gere et al, 2019;Thompson et al, 2021).…”
mentioning
confidence: 99%
“…According to the Pew Research Center's 2021 report on social media use, the majority of young people aged 18–29 year-old, make use of Instagram (76 %), Snapchat (75 %) and TikTok (55 %) ( Anderson and Auxier, 2021 ). Young people use social media for several purposes including entertainment, communication, connecting with peers, education and more recently, to gain health information ( Gere et al, 2020 ; Goodyear and Armour, 2021 ). It has been reported that it is more likely that young people will pose health queries, including mental health queries, through the Internet than through any other means ( Scott et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Innovative ways to improve mental health literacy and help-seeking need to be explored. The stigma surrounding mental health negatively impacts help-seeking and it has been found that individuals are now starting to seek help in spaces with which they are already familiar, such as social media ( Pagnotta et al, 2018 ; Gere et al, 2020 ; Triplett et al, 2022 ). It offers a means to overcome the traditional barriers to help-seeking such as lack of access (including cost and location), a preference for self-reliance and the avoidance of stigma ( Scott et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%